Stroke Affected Lower Limbs Rehabilitation Combining Virtual Reality With Tactile Feedback - Zakharov, Alexander V.; Bulanov, Vladimir A.; Khivintseva, Elena V.; Kolsanov, Alexander V.; Bushkova, Yulia V.; Ivanova, Galina E. (Frontiers in Robotics and AI, 2020)
In our study we tested a combination of virtual reality (VR) with robotics in the original adjuvant method of post-stroke lower limb walk restoration in acute phase using a simulation with a visual and tactile biofeedback based on VR immersion and physical impact to the soles of patients. The duration of adjuvant therapy was 10 daily sessions of 15 minutes each. The study showed the following significant rehabilitation progress in Control (N=27) versus Experimental (N=35) groups respectively: 1.56±0.29 (mean±SD) and 2.51±0.31 points by Rivermead Mobility Index (p=0.0286); 2.15±0.84 and 6.29±1.20 points by Fugl-Meyer Assessment Lower Extremities scale (p=0.0127); 6.19±1.36 and 13.49±2.26 points by Berg Balance scale (p=0.0163). P-values obtained by the Mann-Whitney U test. The simple and intuitive mechanism of rehabilitation, including through the use of sensory and semantic components, allows the therapy of a patient with diaschisis, afferent and motor aphasia. Safety of use allows to apply proposed method of therapy at the earliest stage of a stroke. We consider the main findings of this study that the application of rehabilitation with implicit interaction with VR environment produced by the robotics action has measurable significant influence on the restoration of the affected motor function of the lower limbs compared with standard rehabilitation therapy.